2021
DOI: 10.1002/adom.202002210
|View full text |Cite
|
Sign up to set email alerts
|

Optical Chirality Detection Using a Topological Insulator Transistor

Abstract: of CPL can serve as a molecule-screening tool. In fact, it is widely used in drug screening to discern effective medical target products from ineffective or even toxic enantiomers. [2] The emerging applications in quantum communication and computing, [3,4] circular dichroism spectroscopy, and polarimetric imaging [5] also demand optical chirality detection. However, conventional solutions for optical chirality detection require multiple optical elements including phase retarders, quarter waveplate (QWP), polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…[64,95,97] Very recently Yang et al have reported a device based on 3D TI Bi 2 Se 3 /MoO 3 with responsivity as high as 1.6 × 10 4 and 2.61 × 10 3 AW −1 at 405 and 1310 nm, respectively (Figure 5h). Recent advances in using TMs such as Bi 2 Te 2 Se for optical chirality detection [102] and type-II TDS PtTe 2 for angle-sensitive detection [103] are promising to open up new directions in this field. Nanophotonic devices harnessing the outstanding optoelectronic properties of TIs, Dirac, and Weyl semimetals, have been mostly developed so far using binary, ternary and quaternary Bi and Sb chalcogenides as material platforms.…”
Section: Box 1: Key Characteristics Of a Photodetectormentioning
confidence: 99%
“…[64,95,97] Very recently Yang et al have reported a device based on 3D TI Bi 2 Se 3 /MoO 3 with responsivity as high as 1.6 × 10 4 and 2.61 × 10 3 AW −1 at 405 and 1310 nm, respectively (Figure 5h). Recent advances in using TMs such as Bi 2 Te 2 Se for optical chirality detection [102] and type-II TDS PtTe 2 for angle-sensitive detection [103] are promising to open up new directions in this field. Nanophotonic devices harnessing the outstanding optoelectronic properties of TIs, Dirac, and Weyl semimetals, have been mostly developed so far using binary, ternary and quaternary Bi and Sb chalcogenides as material platforms.…”
Section: Box 1: Key Characteristics Of a Photodetectormentioning
confidence: 99%
“…1,2 The topological surface state with massless Dirac fermions exhibits unique properties of spin-momentum locking ensured by Z2 invariant in three-dimensional (3D) TIs including Bi2Se3. A spin-polarized and defect-tolerant conducting channel of these TIs enables promising electronic, optoelectronic, and spintronic applications, 2,3 such as ultralow-power tunnel transistor, 4,5 opto-spintronics with polarized photocurrent, 6,7 high-performance broadband photodetector, 8,9 and nonvolatile memory by spin-transfer torque. 10 For device applications in transistors or external circuits, contact with metal electrodes plays a crucial role.…”
Section: Introductionmentioning
confidence: 99%
“…The topological surface state with massless Dirac fermions exhibits unique properties of spin-momentum locking ensured by Z 2 invariant in three-dimensional (3D) TIs including Bi 2 Se 3 . A spinpolarized and defect-tolerant conducting channel of these TIs enables promising electronic, optoelectronic, and spintronic applications 2,3 , such as ultralow-power tunnel transistor 4,5 , optospintronics with polarized photocurrent 6,7 , high-performance broadband photodetector 8,9 , and nonvolatile memory by spintransfer torque 10 . For device applications in transistors or external circuits, contact with metal electrodes plays a crucial role.…”
mentioning
confidence: 99%